Ventricular Fibrillation following Varicella Zoster Myocarditis - Adam Ioannou; Irene Tsappa; Sofia Metaxa; Constantinos G. Missouris (Case Reports in Cardiology)
Varicella-zoster virus (VZV) infection can rarely lead to serious cardiac complications and life-threatening arrhythmias. We present a case of a 46-year-old male patient who developed VZV myocarditis and presented with recurrent syncopal episodes followed by a cardiac arrest. He had a further collapse eight years later, and cardiac magnetic resonance imaging (MRI) demonstrated mild mid-wall basal and inferolateral wall fibrosis. He was treated with an implantable cardioverter defibrillator (ICD) and represented two years later with ICD shocks, and interrogation of the device revealed ventricular fibrillation episodes. This case demonstrates the life-threatening long-term sequelae of VZV myocarditis in adults. We suggest that VZV myocarditis should be considered in all patients who present with a syncopal event after VZV infection. In these patients, ICD implantation is a potentially life-saving procedure.